The Potential Use of Carnosine in Diabetes and Other Afflictions Reported in Long COVID Patients - Diniz, Fabiola Cardoso; Hipkiss, Alan Roger; Ferreira, Gustavo Costa (Frontiers in Neuroscience, 2022)
Carnosine is a dipeptide expressed in both the central nervous system and periphery. Several biological functions have been attributed to carnosine, including as an anti-inflammatory and antioxidant agent, and as a modulator of mitochondrial metabolism. Some of these mechanisms have been implicated in the pathophysiology of coronavirus disease-2019 (COVID-19). COVID-19 is caused by severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2). The clinical manifestation and recovery time for COVID-19 are variable. Some patients are severely affected by SARS-CoV-2 infection and may experience respiratory failure, thromboembolic disease, neurological symptoms, kidney damage, acute pancreatitis, and even death. COVID-19 patients with comorbidities, including diabetes, are at higher risk of death. Mechanisms underlying the dysfunction of the afflicted organs in COVID-19 patients have been discussed, the most common being the so-called cytokine storm. Given the biological effects attributed to carnosine, adjuvant therapy with this dipeptide could be considered as supportive treatment in patients with either COVID-19 or long COVID.